A study on the galvanic corrosion of a sol-gel coated PEO Mg-CFRP couple. (1st July 2021) - Ostapiuk, Monika; Taryba, Maryna G.; Calado, Lénia M.; Bieniaś, Jarosław; Montemor, M.F.
Highlights: PEO and a combination of sol-gel and PEO layers were used to mitigate galvanic corrosion between AZ31 and CFRP. Physico-chemical analysis, SVET and OCP measurements were used to study the galvanic coupling effects. CFRP accelerated corrosion of AZ31 when the galvanic couple was formed. The morphology of the PEO layers reduced the barrier protection effect. Combination of an intermediate sol-gel coating and a PEO layer slowed down the corrosion activity in the AZ31/CFRP composite. Abstract: This work investigates the influence of different barrier layers, based on plasma electrolytic oxidation (PEO) and PEO/sol-gel, on the galvanic corrosion between carbon fiber reinforced polymer (CFRP) and the magnesium alloy AZ31. The scanning vibrating electrode technique (SVET) and open circuit potential (OCP) monitoring were combined with microscopic observations using scanning electron microscopy (SEM) to study the galvanic corrosion phenomena at the interface between the Mg AZ31 alloy and the CFRP layers. The PEO and sol-gel layers serving as barrier between AZ31 and CFRP were able to slow down the galvanic corrosion activity providing short-term corrosion protection.